Família-escola: curso de formação para professores pré-escolares de alunos do público-alvo da educação especial - Borges, Laura (2018)
The family and school relationship has been pointed out by many researches as one of the factors favoring the development and learning of students of the target audience of special education (TAEE), especially in childhood. However, the lack of training and information on part of professionals who work with these children on how to attract and involve the family in the school are also highlighted by the studies in the area by turn the relationship difficult. Therefore, this study has as a general objective to plan, implement and evaluate a family and school relationship training course for teachers of pre-school students in the targeted public of special education. The specific objectives were: (a) analyze the family and school relationship, according to the teachers opinion before and after the training course; (b) analyze the family and school relationship according to family members opinion before and after teachers in the training course; (c) analyze the relationship between family and teachers throughout the training course; and (d) assessing the social validity and structure of the training course. Fifteen family members and 15 pre-school teachers from TAEE students from public, private and special schools participated in the study. The data collection took place in three stages: the first one, the pre-test, carried out through a questionnaire to the teachers and their families; the second, the training course, held at the university's premises, consisting of 10 meetings lasting two hours each, applied only to the teachers; and the third stage, the post-test, in which the questionnaire used at the beginning of the research was again applied, in order to verify possible modifications. To perform data collection and respond to the research objectives, in addition to the questionnaire used for the pre- and post-test, field diaries were also used which the teachers completed weekly reporting the established contacts with the relatives of their target student, and the intervention evaluation questionnaire, applied at the last meeting of the course. The qualitative data were analyzed by content analysis and the quantitative data were analyzed through measures of central tendency and dispersion. The results of the pre and post-test of the teachers indicated a discrete increase in the frequency and duration of the meetings with the families. They also started to have more contact with family members, however, the frequency with which they planned these meetings decreased. The variety of media used diminished, prevailing personal contacts. There was an increase in the evaluation of the personal participation, the participation of the family members and the relation established, except for the evaluation of the posture of the families who did not present expressive change. As for the pre and post-test of the families, it was verified an increase in the frequency and duration of the meetings with the teachers, variation in the subjects treated and greater initiative on the part of the teachers for the contact. Teachers started to plan meetings less, while family members began to plan more often. Time is a question present in the factors that hinder and prevent the establishment of contact, being pointed as a factor that could be modified aiming to improve the meetings. In addition, both participants pointed to school-related factors as harmful or impeding the contact, and in the post-test, the families indicated more questions related to themselves. In general, the evaluations of the postures and the productivity of the meetings will vary because of events in the relationship; however, the positive ones remained more frequently. It was noticed that the family had a more positive perception of the teachers, than these had of the relatives. In several situations, the family's satisfaction with the family and school relationship was higher compared to the teachers. In relation to the monitoring of the relationship of dyads through the field diaries, there is a marked individuality and specificity in the cases, preventing generalizations. No substantial changes were identified in the quantities, frequency, and duration of the contacts, and the subjects dealt with the specific situations by which the dyads were passing. The analysis of the teachers regarding the posture of the family and the contact established varied according to the subject treated and the responsible involved. Evaluations were found to be more positive and favorable over the period, with specific cases in which the evaluation decreased due to events in the family. Evaluations were found to be more positive and favorable over the period, with specific cases in which the evaluation decreased due to events in the family. Regarding the social validity and structure of the course, most of the participants stated that they were satisfied, indicating that the course helped in the teaching practice and in the relationship with the families of the student. The negative aspects of the course were punctual and diversified, indicating the group's heterogeneity regarding their preferences and needs, in order to meet the needs that interfered with their practice at that time. By means of the specific modifications identified in the post-test and in the established practical relation, and by the evaluation carried out by the teachers, it is considered that the applied training course model is an interesting and feasible strategy in order to train and inform teachers about the relationship with the families of his students.